Social determinants of health affect disease severity among preschool children with sickle cell disease - Hamda Khan; Guolian Kang; Jerlym S. Porter; Juan Ding; Winfred C. Wang; Jeremie H. Estepp; James G. Gurney; Robert Davis; Jane S. Hankins; Jason R. Hodges (Blood Advances)
Abstract: Individuals with sickle cell disease (SCD) face the burden of managing a lifelong chronic illness, increasing vulnerability to social determinants of health (SDoH). However, how SDoH contributes to health disparities is understudied. We hypothesized that preschool children with SCD living in poor neighborhoods with higher socio-economic distress would experience increased acute care utilization (ACU; described as emergency department visits plus hospitalizations) despite disease-modifying therapy. Participants' home addresses (aged 0-6 years) were mapped using census tract environmental data from the US Department of Agriculture Food Access Research Atlas. In multivariable analyses controlled for sickle genotype and disease-modifying therapies (hydroxyurea and chronic transfusion), SDoH indicators, that is, limited access to food, lack of vehicle, low income, and inadequate education, were associated with higher ACU. Living in households with children >1 mile from a supermarket was associated with more hospitalizations (odds ratio [OR], 1.44; 95% confidence interval [CI], 1.13-1.85) and ACU (OR, 1.37; 95% CI, 1.06-1.80) among children with SCD (aged <6 years). In households with at least 1 bachelor's degree, children with SCD experienced less ACU (OR, 0.67; 95% CI, 0.50-0.93) and hospitalizations (OR, 0.67; 95% CI, 0.49-0.92). Preschool children with SCD with limited access to food and transportation are at a higher risk of acute complications despite receiving free evidence-based therapy and social support. The family education level may have a protective effect. Although SDoH in crowded households and health care maintenance visits were not a focus of this study, future research should consider these factors. Understanding the SCD and SDoH association is crucial for directing resources to improve affected children's health.